Geometrical Characterization And Effect Of Temperature On Graphene Nanoparticles Conductive Ink - Salim, Mohd Azli; Md. Saad, Adzni; Abdullah, Siti Amirah; Wasbari, Faizil; Ali, Murni; Feng Dai (Penerbit UniMAP, 2021)
Graphene nanoparticles (GNP) conductive ink has become the main filler material in the formulation of conductive ink. Because of that, various ef orts have been performed to obtain the influencing parameters that can af ect the GNP conductive ink electrical conductivity. Based on that, this study was performed to investigate the ef ect of temperature, ink thickness, and shape on the sheet resistivity of GNP conductive ink. The ink formulation used was 35 wt% of GNP as filler loading and printed to form 4 types of pattern with 3 dif erent thicknesses by using the stencil printing method. The samples were cured at three dif erent temperatures of 90 °C, 100 °C, and 110 °C, and sheet resistivity was measured to obtain the correlation between the samples’ electrical properties with the temperature, ink thickness, and shape. The results showed that sample of zigzag pattern, with the thickness of 1 mm and cured at 90 °C produced the highest average sheet resistivity of 20.77 kΩ/sq, and a sample of sinusoidal pattern, with a thickness of 3 mm and cured at 110 °C produced the lowest average sheet resistivity of 4.01 kΩ/sq. As for the trend, the increment of ink thickness and curing temperature reduces the sheet resistivity for most of the ink patterns including straight-line, square, and sinusoidal. When the design of the pattern has more curves and bends such as the zigzag pattern, the sheet resistivity value cannot be reduced by increasing the ink thickness and curing temperature. It is because the shape of the pattern becomes the main influencing parameter in determining the ink electrical conductivity.